2009
DOI: 10.1021/jp9052538
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Emission of the Apigenin and Luteolin Flavonoids: A TDDFT Investigation

Abstract: The absorption and emission properties of the two components of the yellow color extracted from weld (Reseda luteola L.), apigenin and luteolin, have been extensively investigated by means of DFT and TDDFT calculations. Our calculations reproduce the absorption spectra of both flavonoids in good agreement with the experimental data and allow us to assign the transitions giving rise to the main spectral features. For apigenin, we have also computed the electronic spectrum of the monodeprotonated species, provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
86
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 50 publications
9
86
0
1
Order By: Relevance
“…These metabolites showed an absorption maximum at 332 nm with a second peak at 260 nm. This, together with the C 15 H 11 O 5 MS/MS fragment, corresponds to apigenin-derived flavonoid structures (Amat et al, 2009). …”
Section: Apigenin-based Flavonoids Show An Inverse Spatial Distributionmentioning
confidence: 90%
“…These metabolites showed an absorption maximum at 332 nm with a second peak at 260 nm. This, together with the C 15 H 11 O 5 MS/MS fragment, corresponds to apigenin-derived flavonoid structures (Amat et al, 2009). …”
Section: Apigenin-based Flavonoids Show An Inverse Spatial Distributionmentioning
confidence: 90%
“…20 It is worth noting that ESIPT can also occur at the API from 5-OH to O-11 in the S 1 geometry, the same way as the QCT. 35 However, for both QCT and API, the S 2 state should be much less susceptible to ESIPT than the S 1 state. 20 Similarly, because the π,π* and n,π* states are close together and the nuclear frameworks are significantly different in these electronic states, internal conversion will occur rapidly.…”
Section: 203637mentioning
confidence: 99%
“…15,19,20 However, contrary to the case of QCT, the ESIPT of API to produce the enol tautomer at the S 1 state cannot occur quickly because the dihedral angle between the B ring and γ-pyrone ring should decrease to cause ESIPT after excitation. 35 Several theoretical studies for API suggest that upon excitation to the Franck-Condon (FC) point, the first relaxation process occurs through molecular planarization. From the FC region, the excited state energy decreases rapidly to a flat region that corresponds to the ESIPT minimum structure.…”
Section: 203637mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, using ab initio CIS/HF, Oumi et al [22] studied chalcone and its hydroxyl derivatives, but the differences reported between gas-phase theoretical and solvated experimental λ max are quite large (0.7eV on average). In recent years, time-dependent density functional theory (TD-DFT) has emerged as a reliable standard tool for the theoretical treatment of electronic excitation spectra and recent works demonstrate the good accuracy for a wide range of systems [23][24][25][26][27][28][29][30][31][32][33][34]. Moreover, the computational cost of TD-DFT calculation is comparative to that of a Hartree-Fock based single excitation theory, such as, configuration interaction singles (CIS) or time-dependent Hartree-Fock (TDHF) method.…”
Section: Introductionmentioning
confidence: 99%